Modeling of the Dynamics Relationship between World Crude Oil Prices and the Stock Market in Indonesia - Adam, Pasrun; Rianse, Usman; Cahyono, Edi; Rahim, Manat (International Journal of Energy Economics and Policy, 2015)
This study aims to examine the dynamics of the relationship between world crude oil prices and Indonesian stock market within the period of January 1st, 2004 to December 31st, 2013. The world crude oil prices referred to the price of West Texas Intermediate crude oil (WTI), whereas the composite indexes at the Indonesian Stock Exchange were used as indicators of the stock market in Indonesia. Daily data were analyzed by employing the LVAR causal model. The test results showed that there was a significant dynamical relationship between world crude oil prices and Indonesian composite index, both in the long-term and in the short-term. The dynamics of this relationship is positive, meaning that if the world crude oil price rises (falls), then the composite index also rises (falls). This finding is in the need for Indonesian government to be considered in their economic policy, as well as for investors to manage their investment portfolio. Keywords: World crude oil price; Stock price; LVAR analysis JEL Classifications: C51; C58; G12; Q41; Q43